(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The financial system in India comprises of Commercial Banks including Public Sector, Private Sector and Foreign Banks, Co-operative Banks, Development Finance Institutions (DFIs) and various other institutions in the areas of Insurance, Mutual Funds and Government Securities. Commercial Banks are playing a very important role in the financial system and payment systems. Banks are ’special’ as financial intermediaries critical for mobilizing public saving and for deploying them to provide safety and return to savers. The deployment of funds mobilized through deposits involves Banks in financing economic activity and providing a lifeline for the payment system. The health of an economy largely depends upon a healthy Banking system, which in turn depends upon a sound asset structure. The banking sector reforms in India during the post-liberalization period, mostly focused on improving the efficiency of the banking sector by incorporating prudential norms for income recognition, asset classification and provisioning and through integrating international standards. In this research paper an attempt is made to examine the sector wise non-performing assets of public sector banks (PSBs) in India and to evaluate the impact of Securitization Act 2002 on sector wise NPAs of PSBs.To examine the objective, the trends in NPAs of Sector wise analyzed before the enactment of the Act (1995-96 to 2001-02) and trends in sector wise NPAs after the enactment of the Act( 2003-04 to 2013-14) with the help of mean, standard deviation and T-test.